Augmented Reality Dissemination and Exploitation Services for Libraries - Koukopoulos, Zois; Koukopoulos, Dimitrios (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
In this work we present a prototype mobile augmented reality system that promotes the dissemination and exploitation of a library’s content and services. The system creates an engaging and immersive ecosystem enhancing the leisure experience for library visitors, allows users to create augmented reality content while visiting the library and attempts to offer personalized services targeting to library visitors’ needs. Visitors are able to purchase a personalized digital version of a book, with respect to the book’s copyrights, thus generating revenue for the library.